2017
DOI: 10.1016/j.cancergen.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Significantly mutated genes and regulatory pathways in SCLC—a meta-analysis

Abstract: Small cell lung cancer (SCLC) accounts for approximately 15% of all lung cancers and demands effective targeted therapeutic strategies. In this meta-analysis study, we aim to identify significantly mutated genes and regulatory pathways to help us better understand the progression of SCLC and to identify potential biomarkers. Besides ranking genes based on their mutation frequencies, we sought to identify statistically significant mutations in SCLC with the MutSigCV software. Our analysis identified several gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 49 publications
1
15
0
Order By: Relevance
“…Since RB1 inactivation accounts for about two-thirds of SCLC patients [21] and amplification of a MYC family gene was found in about one-fifth [31] of SCLC cases, two studies reported on these genetic changes as prone conditions for the use of aurora kinase inhibitors [16,156].…”
Section: Targeted Therapies In Sclc Treatmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Since RB1 inactivation accounts for about two-thirds of SCLC patients [21] and amplification of a MYC family gene was found in about one-fifth [31] of SCLC cases, two studies reported on these genetic changes as prone conditions for the use of aurora kinase inhibitors [16,156].…”
Section: Targeted Therapies In Sclc Treatmentmentioning
confidence: 99%
“…Deficiency of ‘phosphatase and tensin homolog’ (PTEN) is a frequent finding in SCLC but not in NSCLC [168]. Sundaresan et al discovered PTEN deficiencies in 7.4% of SCLC patients [21]. In n = 204 Japanese SCLC tissue samples, alterations in the PIK3CA/AKT/mTOR signaling were analyzed.…”
Section: Targeted Therapies In Sclc Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…SCLC resistance to conventional treatment and its high recurrence rate are primarily due to its markedly high mutation rate and genomic instability (4). A previous study revealed that TP53 and RB transcriptional corepressor 1 (RB1) were the most frequently mutated genes in SCLC, with mutation frequencies of ~85 and 57%, respectively (5). High prevalence of mutations in tumor suppressor genes TP53 and RB1, alterations in chromosome 3p, has been revealed to be significantly correlated with a poor outcome (6).…”
Section: Introductionmentioning
confidence: 99%